What is anti-racism? - Nichols, Hendreich; Wing, Kelisa (Racial justice in America., 2021)
Introduces readers to the concept of anti-racism past and present. Discusses ways that people can become anti-racists. Includes photographs, profiles, sidebars, critical-thinking questions, activities, a glossary, and additional resources.